الأبعاد التاريخية في رواية ثرثرة فوق النيل للروائي نجيب محفوظ - حسني, فتيجة; تواتي إبراهيم, إيمان; بليلة, الزهرة; صالحي, عزيزة (University of Eloued جامعة الوادي, 2024)
يطرح هذا البحث مسألة الأبعاد التاريخية في رواية ثرثرة فوق النيل للروائي نجيب محفوظ، حيث شملت هذه الدراسة عناصر البنية السردية (الشخصيات، المكان، الزمان) مزج فيها الروائي بين الزمن الماضي والحاضر والمستقبل، ليستعيد حوادث التاريخ وينبش الماضي، ليعود إلى الحاضر ويواصل سرده. ومن هنا فإن توزيع هذه الدراسة جاءت في مقدمة وفصلين وخاتمة، احتوى الفصل الأول المعنون بالرواية والتاريخ، مفهوم التاريخ والرواية التاريخية، ثم تطرقنا إلى نشأة الرواية التاريخية ومراحلها أما الفصل الثاني المعنون بتجليات الأبعاد التاريخية في رواية ثرثرة فوق النيل تطرقنا فيه إلى الشخصيات والمكان والزمان. This research raises the issue of the historical dimensions in the novel Gossip over the Nile by the novelist Naguib Mahfouz. This study included the elements of the narrative structure (characters, place, time), In it, the novelist mixed the past, present, and future, to recall historical incidents and excavate the past, then return to the present and continue his narration. Hence, the distribution of this study was in an introduction, two chapters, and a conclusion. The first chapter, entitled “The Novel and History,” contained the concept of history and the historical novel. Then we touched on the emergence of the historical novel and its stages. As for the second chapter, entitled “The Manifestations of Historical Dimensions in the Novel Gossip over the Nile,” we touched on the characters, place, and time.
نقد حديث ومعاصر
Keywords: التاريخ، الرواية التاريخية، نجيب محفوظ، ثرثرة فوق النيل; history; historical novel; Naguib Mahfouz; Gossip over the Nile..